If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 14a = 7 + -1a Solving -8 + 14a = 7 + -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. -8 + 14a + a = 7 + -1a + a Combine like terms: 14a + a = 15a -8 + 15a = 7 + -1a + a Combine like terms: -1a + a = 0 -8 + 15a = 7 + 0 -8 + 15a = 7 Add '8' to each side of the equation. -8 + 8 + 15a = 7 + 8 Combine like terms: -8 + 8 = 0 0 + 15a = 7 + 8 15a = 7 + 8 Combine like terms: 7 + 8 = 15 15a = 15 Divide each side by '15'. a = 1 Simplifying a = 1
| 9x=5x+16 | | 3x+5=23 | | 7-3x=2-8x | | x+9x+2x=180 | | 3x-20+8x=2 | | 3x+2= | | 15-3(2x+5y)= | | 7(x-5)=42 | | 15-2(3x+4y)= | | 4k-(2k-8)= | | 3(3m+3)-16= | | 7x=4x+36 | | 2(3r+8)-12= | | 45.8x+17.1-28.3x-26.6= | | 3y+5.2=2-5y | | 6a=40-2a | | 3x-5x+4x-3+2x= | | 4.2x-2.8+x-1.6= | | -8m-9(5-3m)=12 | | 3.7x-2+x-1.9= | | 2w+4(7+3w)=-14 | | (5y-7)2=18 | | 4w-9(6-5w)=44 | | 5x=2x-35 | | -5(9-x)=-65 | | 2(-4+4x)=-40 | | 2(-8-7x)=152 | | 6t^2+19t-36=0 | | 7(-5-6x)=427 | | 7(9+4x)=175 | | -7(5x-5)=-105 | | 3-6(3x-9)=3(14+35x)-5 |